Anger and Sadness Expressions Situated in Both Positive and Negative Contexts: An Investigation in South Korea and the United States - Song, Sunny Youngok; Curtis, Alexandria M.; Aragón, Oriana R. (Frontiers in Psychology, 2021)
A formidable challenge to the research of nonverbal behavior can be in the assumptions that we sometimes make, and the subsequent questions that arise from those assumptions. In this article, we proceed with an investigation that would have been precluded by the assumption of a 1:1 correspondence between facial expressions and discrete emotional experiences. We investigated two expressions that in the normative sense are considered negative expressions. One expression, “anger” could be described as clenched fists, furrowed brows, tense jaws and lips, the showing of teeth, and flared nostrils, and the other “sadness” could be described as downward turned mouths, tears, drooping eyes, and wrinkled foreheads. Here, we investigated the prevalence, understanding, and use of these expressions in both positive and negative contexts in South Korea and the United States. We found evidence in both cultures, that anger and sadness displays are used to express positive emotions, a notion relevant to Dimorphous Theory. Moreover, we found that anger and sadness expressions communicated appetitive feelings of wanting to “go!” and consummatory feelings of wanting to “pause” respectively. There were moderations of our effects consistent with past work in Affect Valuation Theory and Display Rule Theory. We discuss our findings, their theoretical relevance, and how the assumptions that are made can narrow the questions that we ask in the field on nonverbal behavior.